Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic